Case-based modeling: fostering expertise development and small group learning. Issue 7 (6th August 2019) - Lyons, Paul; Bandura, Randall P.
Abstract : Purpose: This paper aims to present a detailed explication of a learner-centered instructional approach for adults labeled case-based modeling (CBM). The approach is an example of integrative pedagogy aimed at expertise development and is an extension of other instructional approaches, namely, problem-based learning (PBL) and case-based learning (CBL). Design/methodology/approach: The design of the paper contains several integrated components to include: an explanation of the needs and characteristics of the adult learner, comparisons of CBM with both PBL and CBL, a complete theory grounding of the method, a detailed expression of the entire CBM method (phases and steps) for explanation and replication purposes, linkages of CBM with performance, and an empirical test of the CBM method with a sample of employees. Findings: First, the CBM method is an extension of the well-researched methods of CBL and PBL. The script preparation and implementation phases of CBM easily could be appended to either CBL or PBL. Second, the empirical test of the CBM method demonstrates that it may be a positive, efficient tool for education/training with employees, although no significant differences were found in work performance comparisons of CBM-trained employees with traditionally trained employees. Research limitations/implications: The empirical examination has some limitations to include: relatively small sample sizes, lack of demonstration of clear linkage between measures of training performance and measures of job performance, and variations in working conditions of participants. Originality/value: The CBM approach offers to HR practitioners and persons involved with training an efficient yet comprehensive method. The method makes use of script development for the implementation of various interventions, which stimulate performance improvement and development of expertise.